The Cost of Regulation: OSHA, EPA and the Productivity Slowdown. - Gray, Wayne B. (American Economic Review, 1987)
The slowdown in productivity growth in the U.S. economy during the 1970's has been a matter of great concern to policymakers, associated as it is with inflation, unemployment, and declining real wage growth. This paper examines the impact on productivity growth of government regulation, specifically worker health and safety regulation by the Occupational Safety and Health Administration (OSHA) and environmental regulation by the Environmental Protection Agency (EPA). Looking at data for 450 manufacturing industries between 1958 and 1978, the study finds a large, negative relationship between such regulation and productivity growth. Using these results, about 30 percent of the decline in productivity growth in manufacturing during the 1970's may be attributed to such regulation. Several previous studies have looked at the contribution of regulation to the productivity slowdown. Many of these have inferred that the contribution must be small, on the basis of the relatively small amount spent on complying with such regulations. Edward Denison (1979) estimates that only about 16 percent of the productivity slowdown in the 1972-75 period was due to regulation (.35 percentage points out of a slowdown of 2.17 percentage points). Paul Portney (1981) notes that little of GNP is spent on pollution control (under 2 percent), concluding that therefore pollution regulations could have little effect on productivity growth. Norsworthy et al. (1979) also find a small impact of pollution-abatement capital expenditures on productivity growth. Studies based on econometric estimation of the regulation-productivity relationship have found a wide range of results. Gregory Christainsen and Robert Haveman (1981) find regulation reduced labor productivity growth by .27 percentage points, using time-series data and measures of total federal regulation. Robert Crandall (1981) finds a strong relationship between pollution-abatement capital and productivity growth, but this relationship disappears when a measure of energy intensity is included. Robin Siegel (1979) observes a significant contribution (.5 percentage points) from pollution control expenditures to the productivity slowdown for 1965-73, but not for later years. Finally, Frank Gollop and Mark Roberts (1983) examine data for a set of electric utilities and find that regulation of emissions had a large impact on total factor productivity growth, lowering it for regulated firms by .59 percentage points. Many other factors might help to explain the productivity slowdown, including the rise in energy prices, the long and severe recession, and declines in research and development expenditures. There have been a variety of studies examining the contributions of each factor to the slowdown. They generally conclude that many factors contributed to the slowdown, but that a sizable fraction of the slowdown remains unexplained by the estimated contributions of all the factors considered.'